Effect of Alkyldimethylammonium Propansulphonates on Erythrocyte Hypertonic Hemolysis - Orlova, N. V.; Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2004)
The authors investigated the effect of alkyldimethylammonium propanesulfonates with the alkyl chain length of 10 (C10) and 16 (C16) carbon atoms on the erythrocytes susceptibility to the hypertonic stress (4.0 M NaCl). C10 was noted to manifest a high antihaemolytic (AH) activity under erythrocyte hypertonic stress at both 37 and 0°C. The AH values of C16 activity depend on the temperature: at 37°C the substance protects the cells from hypertonic haemolysis, but at 0°C it does not show a significant AH activity.